2006
DOI: 10.1080/08880010600957259
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Cd20 Monoclonal Antibody (Rituximab) for Therapy of Cd20-Positive Nodular Lymphocyte-Predominant Hodgkin Lymphoma in an 10-Year-Old Girl

Abstract: Biologic treatments including antibody-based therapies are still in early-phase development in Hodgkin lymphoma. The authors present the case of a 10-year-old girl with massive, solid, unilateral cervical, nodular lymphocyte-predominant Hodgkin lymphoma. Chemotherapy (doxorubicin, bleomycin, vinblastine, and dacarbazine [ABVD]) and radiotherapy were given, according to the Italian Association of Pediatric Hematology and Oncology (AIEOP) MH-96 study protocol, but the patient failed to enter complete remission. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2008
2008
2012
2012

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…However, in childhood and adolescent nLPHL, except for one case report of the use of RTXB in a 10‐year‐old with refractory advanced stage nLPHL (Culić et al , ), there are no other published reports. As the emerging data from published adult literature on RTXB as first line and salvage therapy in nLPHL is encouraging, its use in childhood nLPHL could be considered as a new treatment option either alone or in combination with chemotherapy or radiotherapy, especially for patients with relapsed or advanced stage disease.…”
Section: Future Directionsmentioning
confidence: 99%
“…However, in childhood and adolescent nLPHL, except for one case report of the use of RTXB in a 10‐year‐old with refractory advanced stage nLPHL (Culić et al , ), there are no other published reports. As the emerging data from published adult literature on RTXB as first line and salvage therapy in nLPHL is encouraging, its use in childhood nLPHL could be considered as a new treatment option either alone or in combination with chemotherapy or radiotherapy, especially for patients with relapsed or advanced stage disease.…”
Section: Future Directionsmentioning
confidence: 99%
“…Since LP cells in NLPHL express CD20, the role of the anti-CD20 monoclonal antibody, rituximab (Rituxan), has been explored in NLPHL in the past few years, starting with a few cases studies such as that reported by Čulić et al [219] in which a pediatric patient refractory to ABVD plus radiation therapy achieved complete remission following rituximab infusion. Zojer et al reported an adult patient with NLPHL who responded to another anti-CD20 antibody, yttrium-90-labelled ibritumomab tiuxetan (Zevalin) [220].…”
Section: Novel Therapies and New Targets For Drug Developmentmentioning
confidence: 99%